High yielding, water use efficient Spanish groundnut (Arachis hypogaea) genotypes for rainfed production system - LAL, CHUNI; HARIPRASANNA, K; RATHNAKUMAR, A L; SAMDUR, M Y (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted in rainy season (kharif) 2002 and 2003 to identify Spanish groundnut genotypes with high yielding potential coupled with in1proved water use efficiency. Considerable genotypic variation was observed among groundnut genotypes for specific leafarea, and soil and plant analysis development (SPAD) chlorophyll meter reading, the 2 traits suggested as surrogates for water use efficiency. Of the 17 Spanish type advance cultures evaluated 1 culture ’PBS 12 i 60’ gave significantly higher pod and kernel yields and oil content of 49.2%. It recorded mean pod yield advantage of 18.70/0 over the national check’JL 24’. Besides high oil contents this genotype also possessed singificantly short plant stature and high number of secondary branches. Low values for specific leafarea, which is negatively associated with kernel yield and high soil plant analysis development chlorophyll meter reading observed for this culture are likely to render it efficient in water use making it suitable for situations where water availability is limited or for rainfed production system.